Impact of Brand Equity on Consumers Purchase Decision of Smart Phone -A Study on University Students in Chittagong, Bangladesh (Global Journal of Management and Business Research, 2020)
This study aims to measure the impact of brand equity on customer satisfaction on the Smartphone in Chittagong, Bangladesh. While conducting this study, the research adopted a model questionnaire for the purpose of doing a survey. In this study 300 respondents have been surveyed, where respondents are the university's student of Chittagong. This study examined the brand equity dimensions developed by David Aaker. A number of statistical tools such as correlation and regression analysis have been applied to analyze the collected data from the survey. Statistical software SPSS (version-22) has been used to make this analysis. The findings of the study reflect that the brand equity dimension such as brand awareness, brand association, perceived quality, brand loyalty have a significant impact on the consumers purchase decisions.
Keywords: brand equity; awareness; brand association; perceived quality; brand loyalty